Residência artística: de ambiente de produção e difusão das práticas artísticas contemporâneas, ou acerca da formação artística e das necessidades de resistência e persistência da pesquisa e experimentação - Moraes, Marcos (Farol, 2021)
reflection based on a case study on the relations between visual arts education and the investigation and work process of artists in residency. Conceptual and historical approaches to artistic residency, as well as an attempt to understand its perspective today